2014
DOI: 10.1038/cdd.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

Glycan-dependent binding of galectin-1 to neuropilin-1 promotes axonal regeneration after spinal cord injury

Abstract: Following spinal cord injury (SCI), semaphorin 3A (Sema3A) prevents axonal regeneration through binding to the neuropilin-1 (NRP-1)/PlexinA4 receptor complex. Here, we show that galectin-1 (Gal-1), an endogenous glycan-binding protein, selectively bound to the NRP-1/PlexinA4 receptor complex in injured neurons through a glycan-dependent mechanism, interrupts the Sema3A pathway and contributes to axonal regeneration and locomotor recovery after SCI. Although both Gal-1 and its monomeric variant contribute to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 60 publications
6
60
0
Order By: Relevance
“…In previous studies, we reported the functional recovery of mice with spinal cord injury (SCI) following local treatment with galectin-1 (Gal-1), a highly conserved glycan-binding protein, through mechanisms involving interruption of Semaphorin3A (Sema3A)-driven inhibitory signals (Quinta et al, 2014b). We found that Gal-1 binds to the Neuropilin-1 (NRP-1)/PlexinA4 receptor complex on the surface of injured neurons through a glycan-dependent mechanism, promoting axonal regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we reported the functional recovery of mice with spinal cord injury (SCI) following local treatment with galectin-1 (Gal-1), a highly conserved glycan-binding protein, through mechanisms involving interruption of Semaphorin3A (Sema3A)-driven inhibitory signals (Quinta et al, 2014b). We found that Gal-1 binds to the Neuropilin-1 (NRP-1)/PlexinA4 receptor complex on the surface of injured neurons through a glycan-dependent mechanism, promoting axonal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Within the CNS, injection of Gal-1 following SCI, binds to the NRP-1/PlexinA4 complex, promoting axonal regeneration and recovery of locomotor activities (Quinta et al, 2014b). However, in spite of considerable progress the molecular mechanisms underlying this neuro-regenerative effect remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that binding of Gal1 to Nrp1 increases the phosphorylation levels of VEGFR-2, thus indirectly implicating formation of a complex multiprotein assembly on the cell surface involving Gal1, glycan-modified Nrp1, VEGF and VEGFR-2. Recently, Quinta et al [9] have shown that Gal1 can play an important role in neuronal regeneration. Gal1, through interactions with Nrp1 prevents semaphorin3A from binding to the Nrp1:plexin complex required to induce neuronal growth cone collapse.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, alternatively-activated M2 microglia prevented inflammationinduced neurodegeneration and abrogated the demyelination process [123]. This inhibitory effect, together with the direct neuroprotective role of Gal-1, mediated by the neuropilin-1 (NRP1)-Plexin A4 complex [124], contributes to promote axonal regeneration, tissue repair and CNS homeostasis. Notably, although exogenous Gal-1 favored an M2 activation phenotype, polarization of human monocytes into M1 or M2 profile was followed by profound changes in intracellular Gal-3, but not Gal-1 expression [125], sug-gesting divergent, although complementary roles of galectins in tailoring macrophage polarization and function.…”
Section: Alternatively-activated M2-type Macrophages and Microgliamentioning
confidence: 95%